A cross sectional study to assess the knowledge, attitude about non-scalpel vasectomy and practices of any contraceptive method among females of reproductive age group in a urban slum, Chennai, Tamil Nadu, 2014 - K., Kokila; K., Chellavel Ganapathi (International Journal Of Community Medicine And Public Health, 2017)
Background: In India, non-scalpel vasectomy (NSV) technique was introduced in 1992 to improve the male participation in family planning, though it has failed to achieve its goal. Hence this study was planned to know the real concern about this condition. This study was carried out to assess the knowledge and attitude about non- scalpel vasectomy (NSV) and practices of any contraceptive methods among married females in reproductive age in an urban slum. Methods: This was a cross-sectional study done in urban field practice area of Institute of Community Medicine, Madras Medical College, Chennai-03, Tamil Nadu in the period July 2014 to August 2014 among Married females of reproductive age group (15-49 years).Specific questions on knowledge, attitude regarding NSV were asked. Data were entered in Microsoft Excel sheet and analysed in SPSS version 20. Results: This is a questionnaire based study. All (106 participants) were aware of vasectomy. Among them 50% knew that vasectomy is an option for permanent sterilization. About 36% of them knew that cash incentive is given for vasectomy & 30% knew that insurance given for pregnancy and other complications followed by vasectomy. Around 31% of the respondents knew that vasectomy does not affect sexual performance. About 29% knew that vasectomy does not need prolonged bed rest. Only 19% of the participants knew that vasectomy is done free of cost and as an OP procedure and 11.3% knew that vasectomy is done without any incision. Among the participants 81% agreed that limiting family size stabilizes the financial condition of the family. About 48% of the participants agreed that family planning is also a responsibility of males and 56% were willing to recommend vasectomy for others. Only 35% of the females agreed to adopt vasectomy for their spouse. Among the respondents 73.6% were practicing some form of contraception currently. Conclusions: We conclude that there is a need to design and develop a need based behavioural change communication strategy to bridge the existing information gap among the eligible couples about NSV & to improve the male participation in family planning. Involvement of media, community participation and successful stories of males who have adopted NSV would enhance the effectiveness of all the interventions.